Ion-conducting membrane, method of preparation and use
Patent Information
- Application Number
- CN202210785955.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-04
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-07-04
AI Technical Summary
然而聚合物成膜过程中,链段随机自由堆积,难以实现可控的离子传输
[0012]本发明离子传导膜可实现在高浓度支持电解液中的阳离子选择性传输。通过不同金属离子与聚合物反应形成离子交联域,从而调控高分子聚合物离子传导膜的内部链段堆积程度,即内部膜结构的致密程度。与特定金属离子反应交联成膜后,链段堆积程度更高(内部更加致密)的离子传导膜可以实现高阳离子传输通道,并且在高浓度盐溶液中依然能保持高阳离子选择性的优势。本发明通过优化金属离子种类、金属离子所处有机溶剂A种类、聚合物所处有机溶剂B种类一系列参数,同时匹配膜厚度与反应时间得到具有上述离子通道可调节的离子传导膜。这种高浓度盐溶液中保持高阳离子选择性的特点,使该离子传导膜在盐水淡化处理中具有潜在应用价值。另外,其作为隔膜用于高浓度盐溶液的碱性锌铁液流电池,可以有效传递荷正电的载流子,实现高离子传导率;同时膜内部高度折叠的链段可提高离子选择性;金属离子交联后提高膜的物理化学稳定性,从而使碱性锌铁液流电池在长时运行中,具有优异的性能。
Smart Images

Figure CN117384401B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ion-conducting membranes, specifically relating to a method for regulating the ion transport channels of an ion-conducting membrane and its application in a high-concentration salt solution battery system. Background Technology
[0002] Controllable ion transport in ion-conducting membranes is crucial for applications requiring specific cation or anion transport, such as electrodialysis membranes in seawater desalination and battery separators. Specific ion transport enables efficient and economical operation of equipment, avoiding resource waste. However, during polymer membrane formation, the random and free stacking of chain segments makes controllable ion transport difficult. It often requires synthesizing polymers with specific ion-selective functional groups to achieve highly selective ion transport channels, significantly increasing the design and manufacturing complexity and cost of separators, thus weakening industrial competitiveness. Summary of the Invention
[0003] To address the aforementioned issues, this invention aims to provide a method for regulating the ion transport channels of an ion-conducting membrane, achieving high cation conductivity in high-concentration salt solutions. By reacting different metal ions with a polymer to form ion cross-linking domains, the internal chain segment stacking degree of the polymer ion-conducting membrane, i.e., the density of the internal membrane structure, is controlled. After cross-linking with specific metal ions, the polymer chain segment stacking degree is higher (the membrane interior is more dense), significantly improving the membrane's selectivity for cations and demonstrating advantages in practical applications involving high-concentration salt solutions. This simple design principle enables controllable ion transport channels in the polymer membrane, promoting membrane functionality diversification and resulting in excellent performance in alkaline zinc-iron flow battery systems with high-concentration salt solutions.
[0004] To achieve the above objectives, the present invention adopts the following technical solution:
[0005] This invention provides a method for regulating the ion transport channels of an ion-conducting membrane, achieving high cation conductivity in high-concentration salt solutions. By reacting different metal ions with the polymer to form ion cross-linking domains, the degree of internal chain segment stacking within the polymer ion-conducting membrane can be controlled. Ion-conducting membranes with a higher degree of chain segment stacking can achieve high cation selectivity.
[0006] The specific preparation steps are as follows:
[0007] (1) Dissolve the metal salt in organic solvent A to obtain a reaction solution with a concentration of 1–1.5 mol / L. -1The transition metal salt is one or more of zinc salt and copper salt; the transition metal salt anion is one or more of chloride ion and sulfate ion; the organic solvent A is selected from one or more of N,N'-dimethylformamide (DMF), N-methylpyrrolidone (NMP), and N,N'-dimethylacetamide (DMAc).
[0008] (2) Dissolve the organic polymer resin in organic solvent B, and stir at room temperature for 24-48 hours to obtain a casting solution; the mass fraction of the organic polymer resin in the organic solvent is 17-20 wt%; the organic polymer resin is one or more of polyvinylimidazole and polybenzimidazole; the organic solvent B is selected from one or more of N,N'-dimethylformamide (DMF), N-methylpyrrolidone (NMP), and N,N'-dimethylacetamide (DMAc).
[0009] (3) The casting solution in step (2) is coated onto a plate with a coating thickness of 50-75 μm. The plate is then quickly immersed in the room temperature reaction solution in step (1) and crosslinked for 10-15 min to obtain the membrane precursor.
[0010] (4) The membrane precursor obtained in step (3) is transferred to a poor solvent of the resin for curing to obtain an ion separation membrane; the poor solvent of the resin is one or more of water, ethanol, and n-heptane; the curing temperature is 15-35℃; and the curing time is 30 min-48 h.
[0011] The ion-conducting membrane has highly effectively folded ion crosslinking domains inside, meaning the internal structure of the membrane is more compact, and it is used in alkaline zinc-iron flow batteries.
[0012] This invention provides an ion-conducting membrane capable of selective cation transport in high-concentration supporting electrolytes. By reacting different metal ions with the polymer to form ion cross-linking domains, the internal chain segment stacking degree of the polymer ion-conducting membrane, i.e., the density of the internal membrane structure, can be controlled. After cross-linking with specific metal ions, an ion-conducting membrane with a higher degree of chain segment stacking (more dense internal structure) can achieve high cation transport channels and maintain high cation selectivity even in high-concentration salt solutions. This invention optimizes a series of parameters, including the type of metal ion, the type of organic solvent A containing the metal ions, and the type of organic solvent B containing the polymer, while simultaneously matching the membrane thickness and reaction time, to obtain an ion-conducting membrane with adjustable ion channels. This characteristic of maintaining high cation selectivity in high-concentration salt solutions makes this ion-conducting membrane a potential application in brine desalination. In addition, when used as a separator in alkaline zinc-iron flow batteries with high-concentration salt solutions, it can effectively transfer positively charged carriers and achieve high ion conductivity; at the same time, the highly folded segments inside the membrane can improve ion selectivity; and the cross-linking of metal ions improves the physicochemical stability of the membrane, thus enabling alkaline zinc-iron flow batteries to have excellent performance during long-term operation.
[0013] The beneficial effects of this invention are:
[0014] 1. This invention provides a method for regulating the ion transport channels of an ion-conducting membrane, which can achieve high cation conductivity in high-concentration salt solutions; it is simple, easy to operate, and scalable.
[0015] 2. The membrane's selectivity for cations gives it excellent performance in alkaline zinc-iron flow battery systems with high-concentration salt solutions; it can effectively transfer positively charged carriers, achieving high ion conductivity; the highly folded segments inside the membrane make the internal structure more compact, which can improve ion selectivity, thus giving the alkaline zinc-iron flow battery excellent performance.
[0016] 3. Metal ion crosslinking improves the physicochemical stability of the membrane, which is beneficial for its long-term stable operation. Attached Figure Description
[0017] Figure 1 The cross-sectional morphology of Example 1(a), Comparative Example 1(b), and Comparative Example 25(c) was captured using a scanning electron microscope.
[0018] Figure 2 Ion transport number assay. The IV curve method was used for the assay.
[0019] Figure 3 Comparison of the cycle performance of symmetrical batteries in Example 1 and Comparative Example 26.
[0020] Figure 4 Long-term stable cycle performance of the alkaline zinc-iron flow battery in Example 1. Detailed Implementation
[0021] The following embodiments are further illustrations of the present invention, but are not intended to limit the scope of the invention.
[0022] Example 1
[0023] 12 g of polybenzimidazole (PBI) was dissolved in 48 g of DMF and stirred at 25 °C for 24 hours to obtain a 20 wt% casting solution. 20.49 g of zinc chloride was dissolved in 100 mL of DMF and stirred until homogeneous to obtain a phase inversion solution. The casting solution was coated onto a glass plate to a thickness of 50 μm. The glass plate was then immersed in the 25 °C phase inversion solution for 10 min to obtain PBI-Z. The glass plate containing PBI-Z was placed in a 25 °C water-curing solution and cured for 24 h to obtain a PBI-Z high ion-selective conductive membrane. The membrane cross-section was photographed using SEM, as shown below. Figure 1 As shown in the figure. The membrane was pre-soaked in 0.033 mol / L KOH for 12 hours, and the ion transport number of the ion exchange membrane was measured by IV curve scanning. The potassium ion (t+) was calculated, and the test results are shown in the figure. Figure 2 As shown (test methods and conditions are referenced in: J. Am. Chem. Soc. 2021, 143, 33, 13135-13144, Dendrite-free Zinc-based Battery with High Areal Capacity via the Region-induced Deposition Effect of Turing Membrane). The t+ value for Example 1 was 0.83.
[0024] After freeze-drying, the hydrogen permeation flux of the membrane was measured to be 0.00037 cm⁻¹. 3 The hydrogen permeation flux is shown in Table 1. The hydrogen permeation flux reflects the degree of chain segment packing inside the membrane. The lower the hydrogen permeation flux, the denser the membrane interior, indicating a higher degree of effective chain segment folding.
[0025] The hydrogen permeation flux test procedure follows the proton exchange membrane test method GB / T20042.3-2009. Sample preparation is as follows: Samples are randomly selected from the same batch, ensuring they are flat and undamaged. Samples are immersed in acetone for at least 1 hour (preferably 2-3 hours, 2 hours in this invention), then dried at 120℃ for at least 2 hours (preferably 2-36 hours, 2 hours in this invention), and ready for use. The testing instrument is a gas chromatograph. The membrane is sandwiched between two stainless steel clamps, each with a gas inlet and outlet (each with a hollow chamber and through-holes on the membrane-facing side). The clamps are sealed (the through-holes are sealed around the membrane surface, with the through-holes facing each other on opposite sides of the membrane), forming hollow, sealed gas chambers on opposite sides of the membrane, serving as the test permeation cells. Hydrogen gas and an inert atmosphere gas (including one or more of inert gases or nitrogen, with nitrogen used in this invention) at a temperature of 25℃±2℃ (25℃ is used in this invention), an air humidity of 50%±5% (50% is used in this invention), and a pressure of 0.05 MPa are introduced into both sides of the gas chamber to equalize the pressure on both sides. After stabilization for 2 hours, the outlet of the inert gas is introduced into a gas chromatograph to detect the permeation rate of the test gas. The effective test area for membrane permeation is circular with a diameter of 10 cm.
[0026] An alkaline zinc-iron flow battery was assembled using the aforementioned separator membrane. The components were stacked in the following order: end plate - bipolar plate - electrode - separator - electrode - bipolar plate - end plate. Adjacent components were sealed with gaskets to prevent leakage. The electrodes were made of activated carbon felt, the bipolar plates were graphite plates, and the effective membrane area was 9 cm². 2 The positive and negative electrolytes are of equal volume, 300 ml each. The positive electrode is an aqueous solution containing 0.4 mol / L sodium ferrocyanide hydrate and 3 mol / L potassium hydroxide; the negative electrode is an aqueous solution containing 0.2 mol / L zinc oxide and 3.8 mol / L sodium hydroxide. The battery cycle efficiency is listed in Table 1, where CE is the coulombic efficiency, VE is the voltage efficiency, and EE is the energy efficiency.
[0027] Operating conditions: High current density 80mA cm -2 After 1.25 hours of charging, the working capacity reaches 100mAh. -2 The charging cutoff voltage is 2.3V, and the discharging cutoff voltage is -0.1V.
[0028] Table 1. Preparation parameters and hydrogen permeation flux of each embodiment and comparative example
[0029] (The preparation process and conditions of each embodiment and comparative example are the same as those of Example 1. The differences from Example 1 are shown in Table 1. Unless otherwise specified, the preparation parameters are the same as those of Example 1.)
[0030]
[0031]
[0032]
[0033]
[0034]
[0035]
[0036] From the numerous examples, comparative preparation parameters, and measured hydrogen permeation fluxes above, it can be seen that to obtain a highly folded internal membrane (a denser internal membrane), the hydrogen permeation flux should be between 0.0001 and 0.001 cm⁻¹. 3 Crosslinked membranes with a flow rate of / min require control from multiple parameters, including: a metal salt with an appropriate reaction rate (Zn in the concentration range of 1–1.5 M). 2+ Cu 2+ The parameters include: appropriate casting liquid solid content (17-20 wt%), film coating thickness (50-75 μm), and the type of organic solvent (DMF, DMAc, NMP) selected for metal ions and organic polymer resins. At the same time, the film thickness and crosslinking reaction time (corresponding reaction time is 10-15 min) are matched.
[0037] When the metal salt is not a zinc or copper salt, as in Comparative Examples 1-3, the cross-linking reaction rate is slow and the degree is low, resulting in a relatively loose interior of the dense membrane and high hydrogen permeation. If there is no metal ion cross-linking, as in Comparative Example 26, the interior of the membrane will be very loose, and the hydrogen permeation will be the highest.
[0038] When the concentration of metal salt is too high, as in Comparative Example 28, it exceeds its solubility in organic solvents, and a uniform phase inversion liquid cannot be formed; when it is too low, as in Comparative Example 27, the degree of cross-linking of organic polymer resin is low, the film has low density and poor mechanical properties, is easily damaged, and cannot be used in practice.
[0039] The effect of casting liquid solid content range on film formation: When the casting liquid solid content is too low, the polymer concentration is low, the film is loose inside, and the hydrogen permeation is too high, such as in the comparative example of 16-24; while when the casting liquid solid content is too high, the polymer is difficult to dissolve, the casting liquid is uneven, and it is impossible to lay the film.
[0040] When the membrane coating thickness is 50–75 μm, the crosslinking reaction time should be 10–15 min. In the data from Comparative Examples 4-9, if the reaction time is too short, as in Comparative Example 4-6, the degree of crosslinking is low, and a dense internal membrane cannot be obtained; if the crosslinking time is too long, as in Comparative Examples 7-9, the casting solution is immersed in the reaction solution, causing the polymer segments to swell with organic solvent B, which also prevents the formation of a dense internal membrane. If the coating thickness is too thin, as in Comparative Example 10-12, the membrane has poor mechanical properties and is easily damaged during practical applications; if the coating thickness is too thick, as in Comparative Example 13-15, the degree of crosslinking is insufficient, and a dense membrane structure cannot be obtained either.
[0041] When organic solvent A and organic solvent B are of different types, the differences in solvent properties, as seen in Comparative Example 25, result in a slow cross-linking reaction rate, leading to large membrane pores and high hydrogen permeation. Alternatively, when other organic solvents are selected, as in Comparative Examples 30-31, the metal salt is almost insoluble, the phase inversion solution concentration is too low, and cross-linking with the polymer resin does not occur.
[0042] Table 2. Selectivity of Examples and Comparative Examples in Salt Solutions of Different Concentrations
[0043]
[0044] Based on the above implementation data Figure 2 It can be seen that as the concentration of the supporting electrolyte increases, as in Example 1 and Comparative Examples 1-2 from 0.03 mol / L... -1 Increase to 3 mol L -1 Comparative Example 1 showed almost no selectivity in both high and low concentration salt solutions; Comparative Example 2 showed a significant decrease in cation transport number from 0.83 to 0.51; while Example 1 showed only a slight decrease in cation transport number, a mere 0.08. This demonstrates that Example 1 still exhibits high cation selectivity in high concentration salt solutions. The supporting electrolyte in the electrolyte primarily enhances its conductivity. While increasing the concentration of the supporting electrolyte improves conductivity, it also weakens the cation transport number of the cation-conducting membrane, thereby reducing the voltage efficiency of the ions.
[0045] Table 3. Applications of each embodiment and comparative example to alkaline zinc-iron flow batteries (test conditions are the same as in embodiment 1 unless otherwise specified)
[0046]
[0047]
[0048]
[0049]
[0050] As can be seen from the implementation data of the above embodiments, the method for regulating the ion transport channel of the ion-conducting membrane proposed in this invention, after cross-linking with specific metal ions to form a membrane, results in a hydrogen permeation range of 0.0001-0.001 cm⁻¹. 3 / min. A suitable range of hydrogen permeation indicates that the density of the polymer chains inside the membrane is within a certain range, which provides channels for ion conduction and can effectively separate substances. At the same time, cross-linking greatly improves the mechanical properties of the membrane.
[0051] In the alkaline zinc-iron flow battery system with high-concentration salt solution, the membrane can effectively transfer positively charged carriers and achieve high ionic conductivity; the highly folded segments inside the membrane can improve ion selectivity; at the same time, compared with the membrane without metal crosslinking (Example 26), metal ion crosslinking improves the physicochemical stability of the membrane, which is conducive to its long-term stable operation, thus giving the alkaline zinc-iron flow battery excellent performance.
[0052] Overall, the battery performance in the comparative implementation data was inferior to that of the example. This is mainly because, when the experimental parameters were changed, the metal ions could not effectively crosslink with the polymer to achieve a dense internal structure of the membrane. The ionic conductivity and ionic selectivity were also inferior to those of the ion-conducting membrane with highly effectively folded ion-crosslinked domains (resulting in a denser internal structure).
[0053] like Figure 1 The images show cross-sections of Example 1, Comparative Example 1, and Comparative Example 25. Comparative Example 25 exhibits obvious loose, sponge-like pores. The difference in the internal structure of the membrane between Example 1 and Comparative Example 1 is reflected in the difference in hydrogen permeability.
[0054] like Figure 2 As shown, the ion transport number test results indicate that Example 1 has a high cation, namely K + Selectivity: The cation transport number (t+) was greater than that of Comparative Example 1 and Comparative Example 2.
[0055] like Figure 3 As shown, in the zinc symmetric battery cycle, Comparative Example 26, which lacks metal ion crosslinking, has poor mechanical properties and cannot withstand dendrite formation during battery operation; while Example 1 has high mechanical properties and can cycle stably.
[0056] like Figure 4 As shown, Example 1 can achieve long-term stable cycling of alkaline zinc-iron flow batteries.
Claims
1. A method for preparing an ion-conducting membrane, characterized in that, Includes the following steps: (1) Dissolve the metal salt in an organic solvent to obtain a reaction solution with a concentration of 1–1.5 mol / L. -1 The transition metal salt is one or more of zinc salt and copper salt; the anion of the transition metal salt is one or two of chloride ion and sulfate ion. (2) Dissolve the organic polymer resin in an organic solvent and stir at room temperature to obtain a casting solution; the organic polymer resin has a mass fraction of 17~20wt% in the organic solvent; the organic polymer resin is one or more of polyvinylimidazole and polybenzimidazole. (3) The casting solution in step (2) is coated onto a plate with a coating thickness of 50~75μm, and then immersed in the reaction solution in step (1) for a cross-linking reaction for 10~15min to obtain the membrane precursor; (4) The membrane precursor obtained in step (3) is transferred to a poor solvent of resin for curing to obtain an ion-conducting membrane.
2. The preparation method according to claim 1, characterized in that, In step (2), the stirring time is 24~48h, and the organic solvent mentioned in steps (1) and (2) is one or more of N,N'-dimethylformamide (DMF), N-methylpyrrolidone (NMP), and N,N'-dimethylacetamide (DMAc).
3. The preparation method according to claim 1, characterized in that, In step (1), the concentration of the reaction solution is 1–1.3 mol L. -1 The cross-linking reaction in step (3) lasts for 12-15 minutes.
4. The preparation method according to claim 1, characterized in that, In step (4), the unsuitable solvent for the resin is one or more of water, ethanol, and n-heptane; the curing temperature is 15~35℃; and the curing time is 30min~48h.
5. The preparation method according to claim 4, characterized in that, In step (4), the curing time is 1 to 4 hours.
6. An ion-conducting membrane prepared by any one of the preparation methods according to claims 1-5.
7. The ion-conducting membrane according to claim 6, characterized in that: The hydrogen permeation flux of the ion-conducting membrane is 0.0001-0.001 cm⁻¹. 3 / min, potassium ion transference number 0.64~0.
83.
8. The ion-conducting membrane according to claim 7, characterized in that: The hydrogen permeation flux of the ion-conducting membrane is 0.0001-0.0005 cm⁻¹. 3 / min.
9. The ion-conducting membrane according to claim 6 or 7, characterized in that: The hydrogen permeation flux test procedure shall refer to the proton exchange membrane test method GB / T 20042.3-2009.
10. The application of the ion-conducting membrane according to any one of claims 6-9 as a separator in an alkaline zinc-iron flow battery.
11. The application according to claim 10, characterized in that: The alkaline zinc-iron flow battery has a positive electrode electrolyte that is a mixed aqueous solution of sodium ferrocyanide and a strong alkali; a negative electrode electrolyte that is a mixed aqueous solution of zinc salt and a strong alkali; the active material in the positive electrode electrolyte is one or both of ferrocyanide and ferrocyanide, and the active material in the negative electrode electrolyte is Zn(OH)4. 2- The concentrations of the positive and negative electrode active materials are 0.01~3 mol L. -1 The positive electrode supports an aqueous solution of potassium hydroxide with a concentration of 0.5–3 mol / L; the negative electrode supports an aqueous solution of sodium hydroxide with a concentration of 0.5–3.8 mol / L.
12. The application according to claim 10 or 11, characterized in that: The electrodes are made of activated carbon felt, and the bipolar plates are made of graphite plates.
Citation Information
Patent Citations
Ion conduction membrane for flow battery and preparation and application thereof
CN110943238A
Method for growing MOF membrane on polymer porous membrane and application thereof
CN112876730A